The Tindih Value of the Sasak Tribe as a Basic Value in Developing Character Education in Schools - Nuraeni, Nuraeni; Suastra, I Wayan; Arnyana, Ida Bagus Putu (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
Character is something that can be educated, built, through effective education both through formal education, non-formal education, and informal. This view intensifies comprehensive character education efforts through various educational channels. Character education built in the education system is character education based on cultural values so that the character of the community will be formed socially. Thus, in understanding the character of a person or a society, it must first be understood the cultural value system that builds it. The tindih value of the Sasask tribe in this case can be applied through a learning model in schools so that students are able to have a positive character that reflects the noble values of the Sasak ethnicity. Tindih values are values that mean motivation to become proper, obedient, and spur, solah, and seleh as the basis of the philosophy of the Sasak community.